Macrophage migration inhibitory factor in major depressive disorder: a multilevel pilot study - Swoboda, Caroline; Deloch, Lena; von Zimmermann, Claudia; Richter-Schmidinger, Tanja; Lenz, Bernd; Kornhuber, Johannes; Mühle, Christiane (International journal of molecular sciences, 2022)
Macrophage migration inhibitory factor (MIF) is a controversially discussed inflammatory marker in major depressive disorder (MDD). While some studies show an association of high MIF protein levels with depression, animal models have yielded conflicting results. Thus, it remains elusive as to whether MIF plays an anti- or pro-depressive role. Therefore, we aimed to examine the potential of MIF at the genetic, expression and protein levels as a risk factor and biomarker to diagnose, monitor, or predict the course of MDD. Patients with a current major depressive episode (n = 66 with, and n = 63 without, prior medication) and remitted patients (n = 39) were compared with healthy controls (n = 61). Currently depressed patients provided a second blood sample after three weeks of therapy. Depression severity was assessed by self-evaluation and clinician rating scales. We genotyped for three MIF polymorphisms and analyzed peripheral MIF expression and serum levels. The absence of minor allele homozygous individuals in the large group of 96 female patients compared with 10-16% in female controls suggests a protective effect for MDD, which was not observed in the male group. There were no significant group differences of protein and expression levels, however, both showed predictive potential for the course of depression severity in some subgroups. While MIF protein levels, but not MIF expression, decreased during treatment, they were not associated with changes in depression severity. This project is the first to investigate three biological levels of MIF in depression. The data hint toward a genetic effect in women, but do not provide robust evidence for the utility of MIF as a biomarker for the diagnosis or monitoring of MDD. The observed predictive potential requires further analysis, emphasizing future attention to confounding factors such as sex and premedication.